Ultrawide-range refractive-index sensor based on asymmetric integrated Y-junction optical waveguide - Phongwisit, P.; Kamoldilok, S.; Limsuwan, P.; Srinuanjan, K. (My University, 2023)
We present a novel ultrawide-range refractive index (RI) sensor based on an asymmetric Y-junction optical splitter. A cylindrically shaped rod with a diameter of 350 nm and a height of 1000 nm with a different RI is inserted into a junction of the asymmetric Y-junction waveguide. This rod serves as a sensing area. Our sensor is simulated using a finite-difference time-domain technique. The splitting ratio is studied for the cases of two operating wavelengths, 1480 and 1550 nm. The results show that the splitting ratio can be described as a parabolic function of the RI of the sensing area at both operating wavelengths. An approximately linear relationship between the splitting ratio and the RI occurs in a narrower RI region of 1.00–1.50, thus enabling to design an ultrawide-range RI sensor. The sensor sensitivities at the wavelengths 1480 and 1550 nm are equal respectively to 0.2653 and –0.4908 RIU–1, with the corresponding R2 parameters amounting to 0.9889 and 0.9777. Our device can serve as an ultrawide-range optical RI sensor for identification of micro-scale biochemical or chemical specimens.
Keywords: integrated photonics; intensity-shift sensors; refractive-index sensors; Y-junction waveguides